Concept Of Aahar By Ayurveda- A Review - Singh, Vd Pankaj Kumar; Malik, Gitika; Verma, Mithilesh (International Research Journal of Ayurveda & Yoga, 2020)
Ayurveda, the science of life, suggested many Siddhantas (principles), One of the most important principles is the three factors that is Aahara (diet), nidra (sleep) and Brahmacharya (celibacy), are mentioned as three Upastambha (sub supporting pillars) for maintaining the health. Ayurveda gives equal importance to Ahara and Vihara. The health of the nation depends on the health of its citizens. Advanced modern medical science has no doubt extended the life span of the human, but the new upcoming health problems are also awaiting their solution. The modern world is currently facing epidemic diseases like diabetes, obesity, heart diseases, infectious disease etc., as a result of stress, improper diet and irregular or sedentary lifestyle. Humans have to suffer many problems related with health in day to day life. Hence the person becomes psychological and physical illness and unable to enjoy full life span. Ayurveda believes that in order to achieve and maintain healthy living (Arogya), it is essential to practice a healthy Vihara like Dinacharya (day regimen), Ratricharya (night regimen), Ritucharya (seasonal regimen), Ahara Vidhi (diet rules), Sadavritta (code of conducts) etc. are described in detail in Ayurveda. Because Ayurveda is mainly based on preventive aspect first rather than curative.